2020
DOI: 10.1111/jvh.13378
|View full text |Cite
|
Sign up to set email alerts
|

Life after hepatitis C cure in HIV‐infected people who inject drugs and men who have sex with men treated with direct‐acting antivirals in France: Health perceptions and experiences from qualitative and quantitative findings (ANRS CO13 HEPAVIH)

Abstract: There remains a substantial gap in our understandings of the life experiences of patients following HCV cure among HIV-HCV-co-infected people who inject drugs (PWID) and men who have sex with men (MSM), two key populations targeted for HCV elimination. We described the experiences and perspectives of HIV-positive PWID and MSM, HCV-cured following treatment with direct-acting antivirals (DAA). We used an exploratory sequential mixed approach using both qualitative data (semistructured interviews with 27 PWID an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…A large body of qualitative research on hepatitis C treatment offers insights into experiences and understandings of hepatitis C cure. While improvements in physical health, such as an increase in energy levels, are significant (Goutzamanis et al, 2021; Mora et al, 2020), experiences of cure are also imbued with deeper meanings. Some research indicates that people affected by hepatitis C primarily value the broader effects of cure such as the relief of not having a looming chronic illness (Mora et al, 2020) and, as such, treatment benefits need to be understood beyond clinical outcomes alone (Goutzamanis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of qualitative research on hepatitis C treatment offers insights into experiences and understandings of hepatitis C cure. While improvements in physical health, such as an increase in energy levels, are significant (Goutzamanis et al, 2021; Mora et al, 2020), experiences of cure are also imbued with deeper meanings. Some research indicates that people affected by hepatitis C primarily value the broader effects of cure such as the relief of not having a looming chronic illness (Mora et al, 2020) and, as such, treatment benefits need to be understood beyond clinical outcomes alone (Goutzamanis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although participants reported small (approximately three points) but significant improvements in mental health‐related quality of life, 36 contrarily, a study among people co‐infected with hepatitis C and HIV reported significantly improved physical but not mental health‐related quality of life at the end of treatment in the sub‐group of people who inject drugs, as measured by the Short Form‐12 Survey. 34 …”
Section: Discussionmentioning
confidence: 99%
“…10 Unlike drug trial data, real-world data present more variable findings on PROs following treatment. [34][35][36] Further, real-world data report on a broader range of PRO measures. A recent German study measured health-related quality of life (Short Form-12 Survey) during and following DAA treatment among people on OST (N = 328), one-third of whom were actively using drugs at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral eradication causes several positive effects: First, the risk of hepatic deterioration due to HCV infection is removed [ 9 ]. Second, patients experience improvement in HRQOL [ 18 , 19 ]. Furthermore, individual viral eradication leads to a reduction of the general burden of HCV infection and reduces further viral spreading [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%